Pengaruh Budaya Organisasi dan Pelatihan terhadap Kinerja Karyawan Dimediasi Komitmen Afektif pada PT Berkah Instalasi Medika: Pengaruh Budaya Organisasi dan Pelatihan terhadap Kinerja Karyawan Dimediasi Komitmen Afektif pada PT Berkah Instalasi Medika - puspita solihatun (Pasca Sarjana Universitas Satya Negara Indonesia, 2025)
This study investigates the influence of organizational culture and training on employee performance, with affective commitment serving as a mediating variable, at PT Berkah Instalasi Medika. The organization has been experiencing a decline in employee performance, primarily attributed to a weak organizational culture, inconsistent training programs, and low emotional attachment among employees. Employing a quantitative approach, the study utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis, with a sample of 215 respondents selected through probability sampling. The findings indicate that both organizational culture and training significantly affect affective commitment. Furthermore, organizational culture and affective commitment exert a significant direct effect on employee performance. However, training impacts performance only when mediated by affective commitment. These results underscore the pivotal role of affective commitment in enhancing the effectiveness of organizational culture and training in improving employee performance.